2022 Joint Rail Conference 2022
DOI: 10.1115/jrc2022-78005
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Modelling and Performance Evaluation of Hydrogen-Powered Heavy Haul Locomotive

Abstract: In recent years, there have been significant activities in the development of hybrid, battery electric and alternative fuel (e.g., LPG, LNG, CNG) locomotives. However, to date there is a limited number of publications on the usage of such modelling and simulation approaches for hydrogen-powered rail vehicles, and almost no publications on hydrogen-powered heavy haul locomotives. A conceptual heavy haul hydrogen-powered locomotive has been designed and studied with the application of advanced simulation techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Hydrogen-powered locomotives emerged initially as a prototype [11] and were further investigated through simulation models [12] and conceptual designs for heavyhaul locomotives [13]. While the overarching consensus in prior studies identified the primary advantage of hydrogen power as its emissions reduction capability, it was simultaneously highlighted that the diesel-electric locomotive showed superior performance due to limitations in the power supply from hydrogen-power units [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hydrogen-powered locomotives emerged initially as a prototype [11] and were further investigated through simulation models [12] and conceptual designs for heavyhaul locomotives [13]. While the overarching consensus in prior studies identified the primary advantage of hydrogen power as its emissions reduction capability, it was simultaneously highlighted that the diesel-electric locomotive showed superior performance due to limitations in the power supply from hydrogen-power units [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A conceptual heavy haul hydrogen-powered locomotive has been designed and studied with the application of advanced simulation techniques used in recent locomotive/train/track dynamics studies. 3 The hydrogen FC power systems such as proton exchange membrane FCs (PEMFCs) and solid oxide FCs (SOFCs), etc. have been theoretically and experimentally studied for the potential applications on rail transportation systems in recent years, and some commercial products have already been used in light rail operations.…”
Section: Introductionmentioning
confidence: 99%
“…A conceptual heavy haul hydrogen-powered locomotive has been designed and studied with the application of advanced simulation techniques used in recent locomotive/train/track dynamics studies. 3…”
Section: Introductionmentioning
confidence: 99%